Perancangan Sistem Informasi Pemberkasan Klaim BPJS Gawat Darurat Menggunakan Microsoft Visual Studio - Yudha Mulya Andara; Yuda Syahidin; Irda Sari (Publikasi Indonesia, 2022)
Hospitals must be able to determine how to carry out a policy in making decisions on the implementation of computerization in health care units by taking into account existing implementation procedures. Medical record filing activities must pay more attention to the completeness of the files in accordance with the needs of the claim, because if one of the filing sheets is not available, the claim may not be accepted. The results of the observations showed that in the emergency service unit, it was found that in processing patient data, they still did manual recording not yet fully computerized. Sometimes when a computerized system is not implemented in processing patient data files, the time for claiming is hampered. The purpose of this study is to describe the BPJS emergency claim filing information system. The research method applied in this research is the development of the waterfall method. The tools used in the system development process are Flowcharts, Data Flow Diagrams (DFD), and Entry Relationship Diagrams (ERD). The results of the analysis of the system design will then be applied to a system to be able to test the feasibility of an application based on Microsoft Visual Studio. Based on this research, it can be concluded that the emergency service procedure policy has not been fully computerized so that it affects other units in BPJS claiming activities.